2017
DOI: 10.2174/1874357901711010083
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Characterization of European Genotype Porcine Reproductive and Respiratory Syndrome Virus Recently Isolated in Mainland China

Abstract: Abstract:Background:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…These two strains are pathogenic to piglets and can lead to classic PRRSV-specific lesions. The infectious pigs showed mild clinical signs and no pigs died, which indicated they are less virulent [ 58 , 63 ]. Interestingly, both of them belong to subgroup I—the Amervac PRRSV vaccine-related strains.…”
Section: The Epidemic Of Prrsv-1 In Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…These two strains are pathogenic to piglets and can lead to classic PRRSV-specific lesions. The infectious pigs showed mild clinical signs and no pigs died, which indicated they are less virulent [ 58 , 63 ]. Interestingly, both of them belong to subgroup I—the Amervac PRRSV vaccine-related strains.…”
Section: The Epidemic Of Prrsv-1 In Chinamentioning
confidence: 99%
“…Interestingly, both of them belong to subgroup I—the Amervac PRRSV vaccine-related strains. HLJB1 and GZ11-G1 show 91.64% and 96.3% genome homology with the Amervac PRRSV virus, respectively [ 58 , 63 ]. Additionally, recombination analyses showed that HLJB1 is a recombinant from the Amervac vaccine and the BJEU06-1 isolate [ 64 ].…”
Section: The Epidemic Of Prrsv-1 In Chinamentioning
confidence: 99%
“…Different PRRSV isolates have distinct pathogenicity. In general, HP-PRRSV isolates have the highest virulence followed by NADC30-like and classical PRRSV2 isolates [11,17,19,41], while current Chinese PRRSV1 isolates are low virulent [8,42]. Retrospective study showed that our XJ17-5 and JSTZ1712-12 isolates were obtained from clinically diseased and healthy pigs, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…However, compared with the large number of PRRSV-2 infections in China, the number of PRRSV-1 infections detected was relatively low (Lin et al, 2020;Zhai et al, 2018). We speculated that the reason might be that PRRSV-1 is not given much attention because it is not the main epidemic strain in China, and there is evidence that most PRRSV-1-infected pigs in China exhibit mild clinical symptoms (Ming et al, 2017;X. Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 98%